Diversity of Azoles Resistant Aspergillus Species Isolated from Experience and Naïve Soils in Nairobi County and Naivasha Sub-County Kenya - Kemoi, Edson K.; Nyerere, Andrew; Gross, Uwe; Bader, Oliver; Gonoi, Tohru; C. Bii, Christine (European Scientific Journal, ESJ, 2017)
New triazole antifungals voriconazole, itraconazole and posaconazole are recommended for prophylaxis and treatment of both invasive and chronic fungal infections such as aspergillosis and aspergilloma. Emergence of azole-resistant among A. fumigatus isolates have been reported in other countries including Tanzania ascribed to either previous antifungal treatment, prophylaxis or triazoles use in agriculture. The use of azole based fungicides in the robust horticulture in Kenya is a significant risk factor for antifungal resistance. The study proposes to analyze environmental isolates of Aspergillus fumigatus, Aspergillus flavus and Aspergillus niger for the presence of resistance against the triazoles antifungals. Fungicide naïve soils were obtained from uncultivated virgin fields while fungicide experience soils were collected from flower, agricultural and horticultural fields and greenhouses within Naivasha sub-county and Nairobi County. The fungal isolates were subjected to antifungal susceptibility to triazoles using broth micro dilution method. A total of 492 samples were analyzed in Nairobi, 52 isolates were identified and they resistance were as follow: A. fumigatus (32%), A. niger (26.09%), A. flavus (33.33%) and A .terreus (0%) and in Naivasha 44 isolates were isolated out of which 25 were A. fumigatus and its resistance was at 36%. Data were analyses using student T test and showed they no different between resistant and susceptible isolates from the two location. Data generated will serve to inform on the current status of triazoles resistance pattern and to raise concern emerging antifungal resistance in clinical practice.